Perceptions of Agricultural Communications Freshmen Regarding Curriculum Expectations and Career Aspirations - Tamra Watson; J. Tanner Robertson (Journal of Applied Communications, 2011)
The purpose of this study was to describe agricultural communications freshmen perceptions of agricultural communications curriculum by describing selected personal characteristics, curriculum expectations and career aspirations of agricultural communications freshmen at Oklahoma State University, Texas Tech University and Texas A&M University. This study also described agricultural communications freshmen’s interests and perceived importance of agricultural communications skills at the selected institutions. The population for the study was 100 agricultural communications freshmen enrolled in an entry-level agricultural communications course during the 2010 Fall Semester. To assess the perceptions of the population, a 54-question instrument was developed and sent to each University and administered on site. Data was collected from each site using scantron sheets and was analyzed using descriptive statistics.
Keywords: curriculum; freshmen; perceptions; aspirations